2020
DOI: 10.1021/acs.chemmater.0c01763
|View full text |Cite
|
Sign up to set email alerts
|

Polyphenylene-Based Solid Acid as an Efficient Catalyst for Activation and Hydration of Alkynes

Abstract: Porous polymer catalysts possess the potential to combine the advantages of heterogeneous and homogeneous catalysis, namely, easy postreaction recycling and high dispersion of active sites. Here, we designed a −SO 3 H functionalized polyphenylene (PPhen) framework with purely sp 2 -hybridized carbons, which exhibited high activity in the hydration of alkynes including challenging aliphatic substrates such as 1-octyne. The superiority of the structure lies in its covalent crosslink in the xyplane with a π−π sta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 57 publications
(92 reference statements)
0
7
0
Order By: Relevance
“…Recently, Wang et al. have shown that a sulfonated PP can hydrate alkyne bonds showing the versatility of such a material [20] . Yet, as the PP POP is made up exclusively of aromatic sp 2 ‐carbons in a ordered structure, it is very robust with inherent high porosity, and these features could make it ideal for applications in high‐pressure reactions like the hydrogenation of CO 2 to formate.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, Wang et al. have shown that a sulfonated PP can hydrate alkyne bonds showing the versatility of such a material [20] . Yet, as the PP POP is made up exclusively of aromatic sp 2 ‐carbons in a ordered structure, it is very robust with inherent high porosity, and these features could make it ideal for applications in high‐pressure reactions like the hydrogenation of CO 2 to formate.…”
Section: Introductionmentioning
confidence: 99%
“…The ratio is set to 1:3 for that raising the content of dibromo molecule will increase the linear content of the polymer, decrease the overall surface area and consequently reduce the accessibility to the bipy sites. [17] The PPhen-bipy is Pd free, as shown in the energy dispersive spectroscopy (EDS; Supporting Information, Figure S1).…”
Section: Resultsmentioning
confidence: 99%
“…The ratio between 5,5′‐dibromo‐2,2′‐bipyridine and 1,2,4,5‐tetrabromobenzene determines the amount of bipy ligands in relation to the PPhen‐bipy polymer, thereby the loading of single metal sites. The ratio is set to 1:3 for that raising the content of dibromo molecule will increase the linear content of the polymer, decrease the overall surface area and consequently reduce the accessibility to the bipy sites [17] . The PPhen‐bipy is Pd free, as shown in the energy dispersive spectroscopy (EDS; Supporting Information, Figure S1).…”
Section: Resultsmentioning
confidence: 99%
“…Wang et al demonstrated a bifunctional acidic solid catalyst, PPhen-SO 3 H, which was obtained through the attachment of –SO 3 H groups to the polyphenylene (PPhen) framework via a post-synthetic modification. 126 PPhen-SO 3 H featuring high porosity and unique structure ensures the high accessibility of reactants to the active sites, representing enhanced activity in the hydration of alkynes with the combination of the solvation environments in the structure.…”
Section: Applications Of Bifunctional Cmpsmentioning
confidence: 99%